Penerapan Gamifikasi Dalam Smart Tourism : Studi Literatur - Asy'ari, Rifqi; Rusdin Tahir; Cecep Ucu Rakhman; Ayu Khrisna Yuliawati (Samarinda State Polytechnic, 2021)
Tourism emphasizes the authenticity of an area with the principle of preservation and sustainable development, but technology is one factor that influences it enough to attract tourists or ease management in the tourism sector. The terminology of smart tourism appears as a direction in the support system for supporters in the tourism sector. One system in implementing smart tourism is gamification, which is still a lot of ordinary people in the system. This article examines the extent of the application of gamification in the concept of smart tourism and what things are still obstacles in the application of gamification in the tourism industry so that it can be a recommendation for further research. So that both are expected to provide an understanding of the application of gamification and the extent of realization in the concept of smart tourism. The method used in this research is a literature study. The results got by the application of gamification in smart tourism are very helpful in the tourism industry. This system provides tourism development, namely providing education, using the potential and use of technology. Gamification is a system where tourists are given more flexibility for activities and interacting with tourist areas, both visually and directly.